RAPORTUL DINTRE LIBERUL ARBITRU ȘI ORIGINEA OMULUI ÎN LUCRAREA PENTRU ORGĂ OP. 78. ȘAPTE VIZIUNI ALE PROFETULUI EZECHIEL (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The relationship between free will and the origin of man in the work for organ op. 78. Seven visions of the prophet Ezekiel.This article aims to present some of the theological-philosophical meanings of the musical work for organ op. 78, Seven visions of the prophet Ezekiel, composed by Carmen Petra Basacopol. Even if the word „visions” appears in the title of this work, the seven sections of this composition are in fact „musical paintings” that bring to attention historical and spiritual realities that emerge from the message of the book and from the prophet Ezekiel: (1) „The heavens opened to me at the river Chebar”, (2) „The vision of the book”, (3) „The visions of the burning coals”, (4) „The vision of the dry bones and their resurrection „, (5)“ The rustling of the cherubim’s wings”, (6) „The heart” and ( 7) „Then the Spirit raptured me”). The brief stylistic analysis of this piece for organ will bring to attention several aspects that will highlight the free nature of the human being based on a biblical vision of creation and divine providence.